Application of the SMARTER Method in Determining the Whitening of Study Permits and Teacher Study Tasks - Rahmat Daffa Affandi; Heny Pratiwi; Azahari; Muhammad Ibnu Sa'ad (Aptisi Transactions On Technopreneurship (ATT), 2023)
Â Study assignment programs and study permits aim to meet the need for staff with certain skills or competencies. in the context of carrying out tasks and functions as well as organizational development, reducing the gap between competency standards and or position requirements with the competencies of Teachers who will fill positions, as well as increasing the knowledge, abilities, skills, attitudes, and professional personality of Teachers, as an integral part of the development plan teacher career. This of course requires a decision support system to be able to assist the Education Office in selecting teachers to provide teacher study permits and study assignments. Decision Support Systems (DSS) or Decision Support Systems (DSS) are computer-based systems that are interactive in assisting decision-makers by utilizing data and models to solve unstructured problems. In this study, the SMARTER method was used as a multi-criteria decision making. The purpose of this research is to assist the Education Office in making decisions when providing a determination of the redemption of study permits, and teacher study assignments as well as providing uniformity and legal certainty in the implementation of study assignments and study permits, and supporting teachers within the local government so that they can improve competence and be more professional in carrying out its duties and functions. Based on research that has been done using the SMARTER method, the sum of each criterion is 0.7840. This implementation produces information that is relatively fast, precise, and feasible to use for updating study permits and teacher learning assignments, and can be carried out without being constrained by time by implementing a web-based application.